Nano Material Innovation in Enhancing Corrosion Resistance of Offshore Structures - Sade, Juswan (Maritime Park: Journal of Maritime Technology and Society, 2024)
Offshore structures are constantly exposed to the corrosive marine environment, causing significant material degradation and potentially jeopardizing structural integrity. This research explores recent innovations in nanomaterial technology to improve the corrosion resistance of offshore structures. The main focus is given to the development of nano-composite coatings incorporating metal oxide nanoparticles and carbon nanotubes. An electrophoretic deposition method was used to apply the coatings on steel substrates, followed by characterization using scanning electron microscopy (SEM) and electrochemical impedance spectroscopy (EIS). Results showed a significant improvement in corrosion resistance, with the nano-composite coatings exhibiting a reduction in corrosion rate of up to 85% compared to conventional coatings. In addition, these coatings exhibited superior adhesion and abrasion resistance in simulated extreme marine conditions. These findings highlight the great potential of nanomaterials in extending the service life and improving the reliability of offshore structures, with important implications for the oil and gas and offshore renewable energy industries.